2019
DOI: 10.1111/jfpe.13040
|View full text |Cite
|
Sign up to set email alerts
|

Improving the flavor of microbone meal with Flavourzyme by response surface method

Abstract: To improve the flavor of microbone meal, Flavourzyme was adopted to hydrolyze the meal and the hydrolysis conditions were optimized with the response surface method. The ANOVA results showed that the degree of hydrolysis (DH) of the microbone meal was significantly (p < 0.05) influenced by the amount of enzyme and hydrolysis time. In addition, the bitter and umami tastes of the microbone meal were significantly (p < 0.05) influenced by hydrolysis time and amount of enzyme, respectively. The optimization result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…The flavourzyme shows great superiority in improving the flavor of protein hydrolysate by producing some MSG‐like amino acids (Du et al., 2017; Y. Zhang et al., 2019). Although there were bitter and sweet amino acids in the bone meal hydrolysate, the taste receptor experiments about interactions between umami and bitterness indicated that the umami substances attenuated bitterness taste (Kim et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The flavourzyme shows great superiority in improving the flavor of protein hydrolysate by producing some MSG‐like amino acids (Du et al., 2017; Y. Zhang et al., 2019). Although there were bitter and sweet amino acids in the bone meal hydrolysate, the taste receptor experiments about interactions between umami and bitterness indicated that the umami substances attenuated bitterness taste (Kim et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Micro bone meal (particles size ≤ 37 µm) was prepared from the backbone of landrace pigs. The crude composition of the pig backbone was 26.7 ± 1.3% water, 27.6 ± 0.3% fat, 17.6 ± 0.5% protein, and 29.1 ± 0.5% ash (Y. Zhang et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations